The Voices of Memory: Silence as a Strategy in Edwidge Danticat's The Dew Breaker (Palimpsesto, 2025)
This research proposes to analyze the relationship between silence and the types of narrators. It examines the concept of silence in the stories "The Book of the Dead" and "The Dew Breaker" by Edwidge Danticat. Throughout this article, the concepts of memory and postmemory will be studied, along with their roles within the two groups of characters. This article explores how each operates depending on the content of the story and how it influences its structure. It will also examine the level of violence to which the protagonists were exposed and their role as victims and/or perpetrators in the context of Jean-Claude Duvalier's dictatorship and forced migration.
Keywords: Danticat; memory; silence